DATING LIME MORTAR BY OSL METHOD, WEST CHERCHELL THERMAL BATHS: A CASE STUDY - Kamel Bouzetine,; Mourad Belaidi,; Zoulikha Tikarrouchine, (International Journal of Innovative Technologies in Social Science, 2025)
The city of Cherchell is known as an ancient city, civilizations have succeeded in the latter from the Phoenicians to the Turkish period. The western thermal baths of this city are little known, Stéphane Gsell attributes their construction to the end of the 2nd beginning of the 3rd century [1] unlike Pensabene [2] which indicates that these dates are not based on any reliable argument, it adds to this problem dating the initial construction, the problem of remodeling during its use or the current plan seems to be symmetrical like the thermal baths of Rome or certain thermal baths in North Africa such as Carthage, Timgad [3]. So in this case an absolute dating is required, the dating of the Arian lime mortar mixed with the quartz sand used for the construction by the OSL dating method used by myself (Bouzetine and all 2021)[4] offers a great possibility of resolving these problems on all that it gives very reliable results.To do this we took samples of lime mortars MC01 from the southern part assumed to be symmetrical to the northern part, MC02 the part assumed to be added later on the west side and mortar MC03 for the assumed initial part.A characterization by SEM-EDX and chemical analysis by fluorescence dates from the late 2nd early 3rd century and the western part was built a little later, the shape of the baths was almost certainly symmetrical.